Creating Sustainable Knowledge Systems: Towards a Risk and Threat Assessment Framework - Jennex, Murray E.; Durcikova, Alexandra (Journal of Strategic Innovation and Sustainability, 2020)
Knowledge is the most important asset to a company. It is key to strategic innovation and alignment, and must be made sustainable. To keep knowledge sustainable, it must be safeguarded. However, knowledge management (KM) and knowledge systems are different than traditional information systems with different threats and operational requirements. Information security professionals recognize that risk assessment is the cornerstone to information security. We build on this perspective and propose that risk assessment techniques need to be applied to KM. We discuss risk assessment frameworks and build on a KM/knowledge system risk assessment framework with a KM/knowledge system specific threat assessment.